Deep neuromuscular block improves angiographic image quality during endovascular coiling of unruptured cerebral aneurysm: a randomized clinical trial. (15th May 2020) - Kim, Bo Young; Chung, Sung Hoon; Park, Seong-Joo; Han, Sung-Hee; Kwon, O-Ki; Chung, Jun-Young; Kim, Jin-Hee
Abstract : Background: Neuromuscular block (NMB) used during general anesthesia induces transient skeletal muscle paralysis, but patient movements during endovascular coiling still occur to some degree. Compared with moderate NMB, deep NMB may further improve the intervention condition during endovascular coiling for unruptured cerebral aneurysms; however, little research has focused on the angiographic image quality. Methods: This prospective, randomized, double-blind clinical trial included 58 patients treated for unruptured cerebral aneurysms with endovascular coiling under general anesthesia. Patients were randomly allocated to either the deep NMB group (post-tetanic count 1 or 2) or the moderate NMB group (train-of-four 1 or 2). The primary outcome was the proportion of patients with a satisfactory intervention condition assessed by surgeons after the procedure using a 5-point intervention condition rating scale (ICRS) from 1 (unable to obtain image) to 5 (optimal); ICRS 5 was defined as satisfactory. Results: There were significantly more cases of satisfactory intervention condition in the deep NMB group than in the moderate NMB group (82.1% vs 51.7%, p=0.015). The frequency of each ICRS score was significantly different between the groups (ICRS 5/4/3/2/1: 23/5/0/0/0 vs 15/9/2/3/0, p=0.035). The incidence of major patient movement requiring rescue muscle relaxant was 10.3% in the moderate NMB group and 0% in the deep NMB group (p=0.237). The drugs used to maintain hemodynamic stability were not significantly different between the two groups. Conclusions: Deep NMB improves the intervention condition during endovascular coiling by improving the image quality.